User Interface Prototype Generation from Agile Requirements Specifications written in Concordia - Pinto, Thiago D.; Gonçalves, Willian I.; Costa, Pablo V. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
User interface prototypes (UIP) are widely used to get feedback before building a software feature. They can prevent misunderstandings between the software development team and other stakeholders (e.g., users, investors) that lead to rework or a resulting software that does not meet their needs. UIP can also be a valuable resource in Agile software development, in which feedback is key. In this paper, we present an approach to generate UIP automatically from Agile requirements specifications written in Concordia and its corresponding prototype tool. The tool is able to generate UIP for web-based applications. We evaluated the approach and the tool with questionnaires, and the results revealed that: (i) the generated UIP are very similar to those drawn by respondents; (ii) the generated source code has good enough quality to be reused by developers; and (iii) they save design and development time.